Nils Petter Gleditsch, Ådne Cappelen og Olav Bjerkholt, The Wages of Peace. Disarmament in a Small Industrialized Economy., PRIO, International Peace Research Institute, Oslo, London: SAGE Publications, 1994, 216 s., £ 45.00. - Heurlin, Bertel (Politica, 1995)
-